KEPEMIMPINAN TRANSFORMASIONAL DALAM KONTEKS ORGANISASI MODERN - Fattahillah; Moh Wahib (PUTRA JAWA PUBLISHER, 2023)
Transformational leadership has become an increasingly interesting topic in management and organizational studies. In the context of modern organizations that are full of change and complexity, transformational leadership emerges as one of the effective approaches to generate positive change and achieve long-term success. This article aims to describe and analyze the concept of transformational leadership in the context of modern organizations. We outline the main theories underlying transformational leadership, as well as key elements that include vision, inspiration, innovative drive, individualized attention, and personal influence.